Positive appraisal style predicts long-term stress resilience and mediates the effect of a pro-resilience intervention - Petri-Romão, Papoula; Mediavilla, Roberto; Restrepo-Henao, Alexandra; Puhlmann, Lara MC; Zerban, Matthias; Ahrens, Kira F.; Barbui, Corrado; Basten, Ulrike; Bayón, Carmen; Chmitorz, Andrea; Felez-Nobrega, Mireia; Kollmann, Bianca; et al. (Nature Communications, 2025)
Stress resilience is the maintenance of mental health despite adversity. Identifying factors that predict and promote good long-term mental health outcomes in stressor-exposed individuals is a first step towards developing more effective prevention programs. In two independent observational samples (N = 132, N = 1034), we find that a tendency to evaluate stressors in a realistic to slightly unrealistically positive fashion (positive appraisal style, PAS) is prospectively associated with resilient outcomes over several years. We also find that PAS is an integrative, proximal resilience factor that mediates the pro-resilience effects of other protective factors (e.g., social support). In an analysis of pre-specified exploratory outcomes of a randomized controlled trial comparing a behavioral intervention targeting a broad set of resilience factors against usual care in a sample of distressed healthcare workers (N = 232; trial registry: NCT04980326), we find that PAS is modifiable, with improvements in PAS mediating intervention-induced improvements in resilience. These results establish PAS as a proximal, plastic, and potentially causal resilience factor.
Gesehen am 26.01.2026